Use of selpercatinib in a patient with RET-mutated non-small cell lung cancer: case report - A. M. Kazakov; K. K. Laktionov; V. O. Vorobyeva; K. A. Sarantseva (Сибирский онкологический журнал)
Background. The use of the modern targeted drugs in patients with non-small-cell lung cancer (NSCLC) with certain somatic alterations (genetic alterations in EGFR, ALK, ROS1, BRAF, RET genes, etc.) provides a significant increase in overall and disease-free survival with an acceptable toxicity profile. The use of RET inhibitors, such as selpercatinib, has significantly improved prognosis in NSCLC patients with RET gene translocation, since chemotherapy and immunotherapy in this cohort of patients are ineffective options. The RET gene translocation occurs rarely (2–3 % of cases among lung adenocarcinoma), but detection of this genetic alteration with subsequent administration of targeted therapy significantly improves the prognosis of the disease. Case report. We present a clinical case of the efficacy of targeted therapy with selpercatinib in a 60-year-old patient with RET-positive NSCLC. Methods to eliminate toxicity after selpercatinib therapy and therapy response are described. Results. Second-line selpercatinib therapy resulted in partial response in our patient with lung adenocarcinoma and the presence of translocation in RET gene. Adverse effects from targeted therapy were minimized or eliminated by the use of concomitant therapy, temporary cancellation of targeted therapy with subsequent dose reduction and gradual return to full therapeutic doses. Conclusion. This case demonstrates the high significance and importance of genetic testing in patients with lung adenocarcinoma not only for the most common mutations, but also for rarer somatic alterations, such as translocation in the RET gene. Detection of this translocation and subsequent administration of appropriate targeted therapy significantly improves the prognosis of patients.